IMPACT OF EQ AND CULTURE OF CONSUMERISM TO INTEREST IN ONLINE SHOPPING BASED ON LIVE STREAMING ON SOCIAL MEDIA - Berupilihen Br Ginting; Nirmalasari; Srie Hartati (SEAN Institute, 2022)
Technological developments penetrate all aspects. Live Streaming on efouria social media is hard to contain. This study aims to see the impact of EQ and consumerism culture on online shopping interest based on Live Streaming on Social Media. Types of quantitative research. The student population of the Politeknik Unggul LP3M Accounting and Computerized Accounting Study program. The sample is 84 students. The study results found that consumerism culture and Emotional Quotient (EQ) had an impact on online shopping interest. The p-sig value is 0.000 < 0.05